PENERAPAN TEORI BRUNER TERHADAP HASIL BELAJAR SEKOLAH DASAR NEGERI 42 PONTIANAK KOTA - Yulyandari, Ika; Halidjah, Siti; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This study aims to describe the application of Bruner's learning theory with the help of pictorial drawings that can improve fraction doubling operations in class V Pontianak 42 Primary School. The research method used is observation and examination of documents in the form of classroom action research. The data source of this research is VA class students, totaling 31 people. And data is the ability of teachers to develop lesson plans, the ability of teachers to conduct learning and assessment of Bruner's learning outcomes and the results of interviews with teacher collaborators. The data analysis technique used is to calculate the average and percentage. This research was conducted in three cycles consisting of three meetings with the results obtained are 1) the teacher's ability to compile learning plans starting from cycle I, 2.81, cycle II was 3.47, and cycle III 3.57; 2) the ability of teachers toconduct learning starting from the first cycle is 2.97, the second cycle is 3.46, and the third cycle is 3.72; 3) assessment of student learning outcomes starts from the first cycle that is 73.4%, the second cycle is 84.10%, and the third cycle is 90.96%. From the data obtainedshows that by applying the Bruner learning theory students can improve learning outcomes in class V 42 Elementary School Pontianak CityKeywords : Application of Bruner Learning Theory, Learning Outcomes, MathematicsLearning